1987
DOI: 10.1007/bf00325288
|View full text |Cite
|
Sign up to set email alerts
|

Central distribution of efferent and afferent components of the pudendal nerve in rat

Abstract: Central distribution of efferent and afferent components of the pudendal nerve was examined in the rat by the horseradish peroxidase (HRP) method after HRP application to the central cut end of the pudendal nerve. The pudendal motoneurons were located in the dorsolateral, dorsomedial and lateral groups at L5 and L6. Each of the dorsolateral and dorsomedial groups constituted a slender longitudinal cell column. Pudendal motoneurons in the lateral group were scattered at L5, rostrodorsally to the dorsolateral gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(85 citation statements)
references
References 86 publications
7
74
0
3
Order By: Relevance
“…Although the development of the SNB has been most intensively studied in rats, a similar sex difference (male > female) in the number of perineal motoneurons is seen in many mammals, including mice, gerbils, dogs, hyenas, monkeys, and humans (Forger and Breedlove, 1986;Wee et al, 1987;Ueyama et al, 1987;Ulibarri et al, 1995;Forger et al, 1996). In those cases in which it has been examined, these sex differences in other mammals also depend on differential exposure to androgens in males and females during development.…”
Section: Motoneuron Death and The Establishment Of Snb Cell Numbermentioning
confidence: 99%
See 1 more Smart Citation
“…Although the development of the SNB has been most intensively studied in rats, a similar sex difference (male > female) in the number of perineal motoneurons is seen in many mammals, including mice, gerbils, dogs, hyenas, monkeys, and humans (Forger and Breedlove, 1986;Wee et al, 1987;Ueyama et al, 1987;Ulibarri et al, 1995;Forger et al, 1996). In those cases in which it has been examined, these sex differences in other mammals also depend on differential exposure to androgens in males and females during development.…”
Section: Motoneuron Death and The Establishment Of Snb Cell Numbermentioning
confidence: 99%
“…The SNB in mature females, who lack or have greatly reduced perineal musculature (Hayes, 1965;ČihĂĄk et al, 1970;Tobin and Joubert, 1991), is comprised of only approximately 60 motoneurons, innervating primarily the external anal sphincter (McKenna and Nadelhaft, 1986;Ueyama et al, 1987). …”
Section: Motoneuron Death and The Establishment Of Snb Cell Numbermentioning
confidence: 99%
“…5,6 Our previous studies suggested that the greater density of descending serotonergic and noradrenergic projections, elicited by the neuroprotective effects of the cellular grafts transplanted into a contusion lesion site, ameliorates of the dyssynergia between the bladder and the urethral sphincter 2-4 by providing some descending control over spinal nuclei and greater descending control over sensory transmission in the DH. [9][10][11][12] The density of bladder afferent projections, that is, CGRP-positive fibers in the DH, is increased after severe SCI [13][14][15] and this has been implicated in detrusor overactivity that develops following SCI. [2][3][4] Bladder afferents in the lumbosacral spinal cord also project to the DH, SPN and dorsal commissure in the lumbosacral spinal cord, 16,17 which was induced by disruption of the descending projections.…”
Section: Normalmentioning
confidence: 99%
“…That robust sustained bladder contractions could not be evoked in the acute SCT cat indicated this low frequency pudendo-vesicle reflex is associated with the AÎŽ afferent fiber mediated spino-bulbo-spinal micturition reflex (Barrington, 1931. In cats, this supraspinal micturition reflex loop involves an initial convergence of pudendal and pelvic afferents in the sacral spinal column (de Groat, 2006, Thor, et al, 1989, Ueyama, et al, 1987, an ascending projection to the pontine micturition center (Blok, et al, 1995), and a descending projection terminating in the sacral parasympathetic nucleus (SPN) (Holstege and Mouton, 2003). As a consequence of the loss of these connections, limited bladder responses are evoked by low frequency pudendal nerve trunk stimulation in the SCI cat and in persons with chronic SCI (Gustafson, et al, 2004.…”
Section: Sustained Bladder Contractions Evoked By Pudendal Afferentsmentioning
confidence: 99%